Membumikan penyusunan laporan keuangan industri perkebunan kelapa sawit menggunakan pendekatan aset biologis berdasarkan PSAK 69 - Emrinaldi Nur DP; Rusli Rusli; Eka Haryani (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2019)
Micro, Small and Medium Enterprises (MSMEs) have become the belle of Indonesia's economic growth. The contribution of MSMEs to GDP in 2018 reached 60.34%. This contribution encouraged the government to further develop MSMEs, including its management aspects such as preparing financial statements. The existence of free trade areas also requires all industries to present their financial reports using international standards, including palm oil industry both large and small, such as MSMEs. Therefore, IAI has issued PSAK 69 concerning agriculture which adopted from IAS 41 using a biological asset approach. However, the PSAK does not show its application to this industry, given the broad scope of agriculture. Through national research grants in 2018, researcher have carried out studies, and produced technical reporting guidelines. At this time, we have already disseminated the findings to oil palm MSMEs. Survey and dissemination for preparation financial reporting used to this activity. This activity were carried out at Kepenghuluan Mukti Jaya, Rimba Melintang District, Rokan Hilir Regency. The results showed that an increasing of understanding to the importance of financial statements in general and the results of financial reports for the oil palm industry in the MSMEs target area.